Trajetórias afetivo-sexuais entre jovens do ensino médio: implicações dos sentidos de amor e maternidade - Torres, Taluana Laiz Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Esta dissertação de mestrado se insere na Linha de Pesquisa Processos Formativos, Diferença e Valores, em uma vertente comprometida com estudos sobre os saberes, práticas e representações que permeiam as relações escolares, considerando-se, de forma particular, os aspectos referentes às questões de gênero, sexualidade, classe, raça e geração. A pesquisa tem como objeto o estudo das trajetórias afetivo-sexuais de seis jovens estudantes do Ensino Médio de uma escola da periferia urbana de Presidente Prudente/SP, com idade entre 15 e 18 anos. Interessa aos estudos em educação, preocupados com o formação para a vida sexual do(a)s jovens, o reconhecimento de todos os elementos envolvidos com a vivência da sexualidade. Considera-se que, entre estes, existe um aspecto pouco privilegiado nas investigações: aqueles que são referidos aos sentimentos, emoções, desejos e idealizações dos indivíduos. Portanto, objetivou-se tomar o contexto das emoções como elemento central na análise das experiências afetivo-sexuais vividas por essas jovens, o que implicou a interpretação dos significados que cabem aos sentimentos, sonhos e idealizações em torno da maternidade e do amor romântico. Estes foram relacionados com as suas declarações acerca de seus comportamentos, práticas e projetos de vida. A iniciação sexual e afetiva, em suas modalidades do ficar, do namoro, da primeira vez, da gravidez, da vida conjugal e do casamento foram focos especiais de atenção no caminho da pesquisa. Foram utilizados os referenciais teóricos dos estudos sócio-históricos e culturais, para interpretar as múltiplas possibilidades de viver e pensar a experiência amorosa, em um lugar e tempo sócio-históricos determinados.

The present Master's Dissertation concerns the Research Line in Formative Processes: Differences and Values to a field committed to the knowledge, practice and representations involving school relations which, in a particular way, accounts the concepts concerned to gender, sexuality, class, race and generation issues. The aim of this work is to study the affective-sexual pathways of six High School young students from an urban periphery of Presidente Prudente, SP, with ages between 15 to 18 years. Concerned with the sexual maturation of the young students, the recognizing of all issues connected with the experience of sexuality is of interest within educational studies. Among them, less privileged aspects of the study were considered; the ones related to feelings, emotions, desires and idealization of individuals. Therefore, the context of emotions was regarded as a main element for the affective-sexual experience analysis experienced by these young girls leading to the interpretation of feelings, dreams and idealizations related to motherhood and romantic love issues, further regarded to their statements in behavior, practices and projects of life. The relationship-sexual initiation towards its modalities of personal relationships; making out, dating, first sexual experience, pregnancy, marital life and marriage were specially highlighted in this study. Theoretical references from socio-historical and cultural studies were used to explain the multiple possibilities for the living and thinking concerning sexual experience within a given socio-historical time and place. Methodological procedures of this study are connected to qualitative approaches of ethnographic nature, and questionnaires, records of direct observations in field notebook and semi-structured interviews are regarded as data collection basic tools. Results obtained in the present study show that juvenile sexuality had been reported as a learning process concerning the emotional.
Keywords: Educação; Ensino médio; Maternidade; Affective; Sexual pathways; Youth; Motherhood